1997
DOI: 10.1046/j.1471-4159.1997.68010419.x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Ca2+‐Dependent Protein Tyrosine Phosphorylation in Carbachol‐Induced Phospholipase D Activation in Rat Pheochromocytoma PC12 Cells

Abstract: Abstract:The mechanism for carbachol (CCh)-induced phospholipase D (PLD) activation was investigated in [3H]palmitic acid-labeled pheochromocytoma P012 cells with respect to the involvement of protein tyrosine phosphorylationand Ca2~. PLD activity was assessed by measuring the formation of [3H]phosphatidylbutanol in the presence of 0.3% butanol. Pretreatment of cells with the tyrosine kinase inhibitors herbimycin A, genistein, and tyrphostin inhibited PLD activation by CCh. Western blot analysis revealed sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Monolayer cultures of PCI2 cells were maintained in 100-mm-diameter tissue culture dishes in growth medium composed of Dulbecco's modified Eagle's medium supplemented with 10% (vol/vol) fetal bovine serum and 5% (vol/ vol) horse serum (Kanoh et al, 1992;Ito et a!., 1997a).…”
Section: Cell Culturementioning
confidence: 99%
“…Monolayer cultures of PCI2 cells were maintained in 100-mm-diameter tissue culture dishes in growth medium composed of Dulbecco's modified Eagle's medium supplemented with 10% (vol/vol) fetal bovine serum and 5% (vol/ vol) horse serum (Kanoh et al, 1992;Ito et a!., 1997a).…”
Section: Cell Culturementioning
confidence: 99%
“…This is indicated by numerous observations that vanadate in combination with H 2 O 2 , or PAO, stimulates phospholipase D activity in vivo (Bourgoin and Grinstein, 1992;Kumada et al, 1994;Kumada et al, 1996;Min et al, 1998;Taher et al, 1998). Further support comes from the observations that tyrosine kinase inhibitors such as genistein, herbimycin or tyrphostin, inhibit phospholipase D activation in several cell types (Uings et al, 1992;Schmidt et al, 1994;Ward et al, 1995;Jinsi et al, 1996;Natarajan et al, 1996;Ito et al, 1997;Exton, 1999). These reports prompted us to investigate whether phospholipase D activity is involved in PTPase-inhibitor-induced PKCβII reverse translocations.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the inhibitors decrease the activation of PLD by ATP in U937 promonocytes Kusner et al 1993), thrombin in platelets (Martinson et al 1994), FMLP in neutrophils or Iti.60 cells (Uings el al. 1992;Itoule et al 1999), endothelin 1, norepinephrine and angiotensin II in vascular smooth muscle cells (Wilkes et al 1993;Jinsi et al 1996;Suzuki et al 1996b), bombesin in fibroblasts (Briscoe et al 1995), carbachol in PC12 pheochromocytoma cells and ItEK cells expressing the M3 muscarinic receptor (Ito et al 1997a;Schmidt et al 1994) and endothelin 1 in myometrium (Le Stunff et al 2000b).…”
mentioning
confidence: 99%
“…19, Gomez-Cambronero 1995;Ito et al 1997b;Marcll et al 1997;Min et al 1998a). Although the tyrosine phosphorylation of cellular proteins was correlated with the activation of PLD, the tyrosine phosphorylation of PLD itself was not (Bourgoin & Grinstein 1992;Ito et al 1997aIto et al , 1997bMin et al 1998a). Furthermore, the effects ofPKC inhibitors and PKC down-regulation indicated that PKC mediated most of the PLD activity change seen with HzO2 in Swiss 3T3 cells (Min et al 1998a) although not in endothelial cells (Natarajan et al 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation